A REVIEW OF JOB STRESS AND ITS INFLUENCE ON HEALTH-RELATED RISK - Nur’Aina Samaniah Binti Osman; Siti Musliha Binti Mohd Idris; Nurul Nabilah Binti Shaare; Mira Aishwarya Ain Mira Hussein; Wan Khayrina Sofiya Binti Mohd Hasnurizal; Nurul Illya Batrisya Binti Aziz (International Journal of Accounting, Finance and Business, 2022)
Job stress can contribute to a variety of health issues. For instance, heart diseases,psychological health, and cardiovascular disorders are examples of health-related problemscaused by job stress. Job stress is a common reaction that arises when the workload increasesto the point of becoming excessive. This review study is intended to add information andliterature on the job stress and its influence on health-related risk. Through literature review,it will focus on job stress issues that lead to health-related risk and how preventive action canbe taken to reduce job stress. Based on the review from the selected articles, there are 23 healthrisks or health problems that we observed such as lack of appetite, increased heart rate anddiabetes and 16 preventions that have been taken from 20 articles. For example, sleep on time,engaging in hobbies and gatherings. As individuals, we must be able to cope with and managework-related stress because even if you are enthusiastic about what you do, any profession mayhave stressful parts. Work-related stress, on the other hand, can become overpowering when itbecomes chronic, causing harm to both physical and emotional health and will become a longtermillness if not taken care of quickly. This review will provide as a guide or benefit formanagers and employers in planning for a healthy workplace and positive preventive measures.